Entrepreneurial Marketing Impact Score on MSME Performances Through Its Dimension - Mediany Kriseka Putri; Andriani Natasha Putri (Faculty of Economic and Business, 2023)
The presence of the entrepreneurial marketing concept is considered capable of overcoming marketing problems in MSMEs. This study aims to determine the specific magnitude of the influence score given by each entrepreneurial marketing dimension to MSMEs in Bengkulu City. This study focuses on culinary MSMEs that are the mainstay sector of the region. The effective and relative contribution has been used to measure the influence score of its dimension on performance and 183 questionnaires are distributed to the owners of MSMEs in Bengkulu City. The results show that the dimension of resource leverage most dominantly affects business performance. Meanwhile, calculated risk-taking has a minor effect. Essentially, culinary MSME business actors in Bengkulu City must improve their ability to effectively predict the problem in the future that can be done by joining risk management certification or webinar.JEL Classification: L25, L26, L66How to Cite:Putri, M. K., & Putri, A. N. (2023). Entrepreneurial Marketing Impact Score on MSME Performance Through Its Dimension. Etikonomi, 22(1), 79–92. https://doi.org/10.15408/etk.v22i1.25617.